Relevansi Hukum Administrasi Negara Sebagai Instrumen Mewujudkan Pemerintahan yang Responsif - Fauzan Zakir (Journal of Global Legal Review, 2025)
State Administrative Law plays a strategic role in guiding government administration to respond appropriately and responsibly to the needs and dynamics of society. Responsive governance requires not only swift action but also adherence to the principles of legality, accountability, and protection of citizens' rights. This study aims to analyze the relevance of State Administrative Law as an instrument for realizing responsive governance within a democratic constitutional state. The research method used is normative legal research with a statutory and conceptual approach. The results indicate that the general principles of good governance, regulations regarding discretion, and mechanisms for oversight of state administrative administration and judicial administration are important instruments in ensuring the responsiveness of government actions and decisions. However, in practice, challenges remain, such as tensions between demands for responsiveness and legal certainty, limited capacity of the apparatus, and a suboptimal understanding of the principles of State Administrative Law. Therefore, strengthening norms, improving the quality of the apparatus, and consistent application of the principles of good governance are key prerequisites for realizing responsive and just governance.